Participating in Change: Engaging Student Veteran Stakeholders in Advocacy Efforts in Clinical Higher Education. (May 2021) - Dobson, Caitlin G.; Joyner, Jordan; Latham, Alex; Leake, Valerie; Stoffel, Virginia C.
Two independent research teams led by graduate students from clinical disciplines studied the lived experiences of student veterans transitioning from the military into higher education. Additionally, these projects provided graduate students with training in the research process, application of evidence-based practice in preparation for professional responsibilities and advancement, and collaboration with student veteran stakeholders as coinvestigators and project team members. One study piloted a student veteran orientation course with the aid of veteran stakeholders to better address the overall needs of student veterans on campus. The other study engaged student veteran participants as coinvestigators using the photovoice methodology to illuminate their perspectives on social relationships. Findings in each study added greater depth to previously discovered trends, and revealed insights into student veteran educational priorities, the impact of the transition process on social roles and relationships, graduate research project design, and community advocacy. This study added insight into the factors that affect student veterans' higher education experience, which can be used to inform future studies conducted at the graduate level, examine interdisciplinary approaches to research and advocacy, amplify the voice of student veterans, and encourage interaction in research between civilian and veteran students.